OBLIGATION TO LABEL NON-HALAL PRODUCTS IN HALAL PRODUCT ASSURANCE SYSTEM IN INDONESIA - Farid Wajdi (International Journal of Synergy in Law, Criminal, and Justice, 2024)
The mandatory labeling of non-halal products is a crucial element of the Halal Product Assurance system in Indonesia as stipulated in Law Number 33 of 2014. This study highlights normative, technical, and consumer protection aspects, including the inclusion of the “non-halal” statement on packaging, material color indicators, and the basis of sharia legitimacy through Islamic jurisprudence (fiqh) principles. Using a qualitative approach, using analysis of legal documents, academic literature, and comparative studies with countries such as Malaysia and Turkey, this study found that non-halal labeling increases legal certainty, transparency, and consumer trust while reducing the risk of misleading claims. This study recommends strengthening fatwa registration, harmonizing procedures, and improving LPH accreditation to strengthen the credibility and efficiency of the JPH system in Indonesia